Social-Cultural Environment and Performance of Donor Funded Health Projects in Kenya - Mobegi, Jones Ong’era; James, Rosemary; Sang, Paul (European Scientific Journal, ESJ, 2020)
This study provides an empirical investigation on the effect of the social-cultural environment; local community literacy levels, support from local communities, language, and corruption levels on the performance of donor-funded health projects in Kenya. Empirical evidence indicatesthat most donor-funded health projects in Kenya experience time and cost overruns as well as quality issues. This study investigated a population of 69 donor-funded health projects that were initiated between 2008 and 2018 and were ongoing during the study period. A census study was conducted to ensure efficiency, representativeness, reliability, and flexibility since the population was small. The study adopted explanatory and descriptive research designs. Regression results indicated that language, support from the local communities, and the level of literacy in the local communities had positive relationships with the performance of donor-funded health projects in Kenya with coefficients of 0.021, 0.045, and 0.042 respectively. These factors were significant at a 5 percent significance level with p-values of 0.018, 0.019, and 0.047 respectively. Corruption levels had a negative relationship with the performance of donor-funded health projects in Kenya with a coefficient of - 0.031 that was significant at a 5 percent significance level with a p-value of 0.013. The study recommends that the government develops policies and frameworks that will help projects to minimize the negative effects of the social-cultural environment and enhance the positive effects, and that all decision-makers and other donor-funded health project stakeholders devise policies and strategies for controlling the effect of the social-cultural environment on the donor-funded health projects.